GROB G 120 TP-A AIRCRAFT BETA SYSTEM ANALYSIS USING FTA (FAULT TREE ANALYSIS) METHOD - Rahmawati, Fajar Khanif; Priyahapsara, Istyawan; Funny, Rindu Alriavindra; Wati, Denisa Trisma (Institut Teknologi Dirgantara Adisutjipto, 2023)
Grob G 120 TP - A beta system aircraft is a system that regulates the size of the angle on the propeller. 42 failures occurred in the beta system from August 2016 to May 2021, resulting in the beta system having to be replaced even before reaching its 2500 flight hour age limit. Using the FTA (Fault Tree Analysis) method, which begins with defining the failure and determining the boundary conditions of the beta system, describing the fault tree model, identifying the minimum cut set from the fault tree, performing a qualitative analysis of the faults tree, and doing a quantitative analysis of the fault tree, it can be seen that the failure that often occurs in the beta system of the Grob G 120 TP-A aircraft is the occurrence of high oil temperature over 84 ℃, the qualitative analysis found 12 causes of failure on the beta system, and based on quantitative analysis obtained probability the occurrence of beta system failure is 0.76363.